Fieldwork in the human services : theory and practice for field educators, practice teachers and supervisors - Cooper, Lesley; Briggs, Lynne (St Leonards, N.S.W : Allen and Unwin, 2000)
Teaching, learning and assessment in the field. The responsibilities of fieldwork management. Practical suggestions.
Keywords: Social service; Human services; Field work; Social service -- Field work; Social work education; Social service -- Field work -- Study and teaching (Higher); Human services -- Study and teaching (Higher); Field work (Educational method)